2023
DOI: 10.1609/icwsm.v17i1.22122
|View full text |Cite
|
Sign up to set email alerts
|

The Pursuit of Peer Support for Opioid Use Recovery on Reddit

Abstract: Individuals suffering from Opioid Use Disorder and other socially stigmatized conditions often rely on peer support groups to find comfort and motivation while treating their condition. Many may face barriers in accessing peer support treatment, such as shame and social stigma, seclusion, or mobility restrictions. In this study, we quantitatively characterize the potential of the Reddit community in offering these individuals an online alternative to receiving peer support. By analyzing the social interactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…We are interested in understanding whether this declared change in opinion is related to a change in information consumption behavior in the future. Previous work (Massachs et al 2020;Balsamo, Bajardi, and Panisson 2019;Balsamo et al 2023) has showed that participation in subreddits is a valuable proxy for a wide range of characteristics of the user. For this reason, we take the subreddits they participate in-their communities on Reddit-as a meaningful measure of the behavior of the user.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…We are interested in understanding whether this declared change in opinion is related to a change in information consumption behavior in the future. Previous work (Massachs et al 2020;Balsamo, Bajardi, and Panisson 2019;Balsamo et al 2023) has showed that participation in subreddits is a valuable proxy for a wide range of characteristics of the user. For this reason, we take the subreddits they participate in-their communities on Reddit-as a meaningful measure of the behavior of the user.…”
Section: Datamentioning
confidence: 99%
“…Furthermore, we limit the time frame in which we observe behavioral change by considering only comments written at most one year before or after the date of the user's post on CMV. We do so in order to consider in our analyses only events of online behavior change that are relatively close in time to the reported opinion change, and that can thus be considered related to it more reliably (Balsamo et al 2023). We indicate with b u,s and a u,s the number of comments authored by user u on subreddit s before and after (respectively) their post on r/ChangeMyView, limited to the time frame described above.…”
Section: Datamentioning
confidence: 99%
“…Nevertheless, the data from social media are invaluable for research. The information gathered from social media platforms is timely and relevant for studying substance use characteristics longitudinally [ 17 - 19 ]. As a result, the data obtained from social media offer a unique opportunity to observe substance use behaviors within a broad population, enabling a deeper comprehension of the underlying patterns and factors influencing substance use behaviors.…”
Section: Introductionmentioning
confidence: 99%